Kajian Distribusi Pemasaran dan Harga Pokok Produksi Karet Rakyat di Kalimantan Selatan - M. Nordiansyah; Kadir Kadir; Doni Stiadi (JURNAL BISNIS DAN PEMBANGUNAN, 2018)
This research was conducted to study on marketing distribution and analyze cost of rubber production in South Kalimantan Province. The research focused to farmers in Balangan Regency.Research showed that the marketing distribution of rubber from farmers to factories went through several stages. The rubber is sold by farmers to small collectors, small collectors sell to large collectors, large collectors sell rubber to the factory. Farmers have not calculated the cost of production of rubber. The selling price does not consider the cost, it based on the market price. Farmers still sell the rubber to the collectors, when the price decrease. Cost calculation analysis is needed to find out how the actual costs incurred by farmers in an effort to produce rubber. So it is known how much is actually a decent price for farmers to sell rubber. During 2017, the selling price of rubber decreased, below the cost of production at the farmer. Keywords: Cost of product, Rubber, Production